Auditoría de control interno y su incidencia en las cuentas por cobrar de la asociación de militares paracaidistas en S/P “Gral. Carlo Magno Andrade”, cantón Quevedo, año 2012 - Orosco Mala, Erika Tatiana (2015)
The Asociación de Militares Paracaidistas en S/P “Gral. Carlomagno Andrade”, canton Quevedo, is devoted to the benefit of money and the collection of partners' monthly quotas for the amplification improvement and benefit of the same ones. The present Audit of internal control and their incidence in the bills to get paid of the Association of Military Parachutists in S/P "Gral. Charlemagne Andrade", he/she was carried out with the purpose of examining the level of execution of the laws and applicable regulation to the Association, to check the level of truthfulness from the information to the item bills to get paid, to evaluate the grade of efficiency of the operations of the same one. The obtained information provided the directive of the association a white he/she devises of the current situation that is crossing as for the internal execution of the you pose you and financial activities. To make the work it was used investigation methods like; inductive, deductive, and analytic, while the types are; descriptive, explanatory, the techniques were constituted by interviews, surveys and work papers. After having carried out the study it was possible to examine the level of I execute of the laws and regulations in 50%, the level of truthfulness of the information giving 33.33% as a result, it was demonstrated that the grade of efficiency of the operations of the bills to get paid corresponds in 3.14%. That which is recommended to Settle down technical and procedures that allow the improvement of the control of the information generated by the activities of the association; which will be executed by vicarial people, to make with the evaluations making use of technical and procedures that allow to determine the correct execution of internal control stop this way to check their level of truthfulness in the information, to fulfill to cabalidad the normative ones effective to study them and to put them in practical, so that this bears to that the information that is managed in the association is reliable, reasonable and opportune and this way to be able to take a good control in the handling of the bills.